UPACARA TUMPEK WARIGA DI BALI DALAM PERSPEKTIF TEORI KEBUDAYAAN VAN PEURSEN - I Gusti Ngurah Agung Panji Tresna (UHN IGB Sugriwa Denpasar, 2022)
Bali cannot be separated from traditional and religious ceremonies, which causes Bali to have a charm that can make people interested and amazed. The island of Bali is known as a tourism area due to its customs and culture. Balinese people do not escape the Yadnya ceremony (sincere offerings). All of the yadnya ingredients used to come from agricultural products that were offered to God as a form of devotion, known as the Tumpek Wariga Ceremony. Van Peursen's mythical thinking can be correlated with local cultural thought in the Tumpek Wariga ceremony, Van Peursen's theory also includes ontological aspects in the concept of natural harmony (Tri Hita Karana) which explains the existence of Parhayangan which means maintaining a harmonious relationship with the creator or God Almighty. , then there is what is called Pawongan which means maintaining a harmonious relationship with all living things and the last one is Palemahan which means maintaining a harmonious relationship with the natural environment. Humans develop the essence of the celebration of Tumpek Wariga by building awareness of the vital role of plants which is summarized in the palemahan concept as a protection system for the natural environment. The scheme in Van Peursen's theory here is seen in the Tumpek Wariga ceremony process which in the end humans must always maintain and harmonize nature contextually.